The Profits of Wisdom : The Impacts of a Business Support Program in Tanzania - Bardasi, Elena (World Bank, Washington, DC, 2017)
Business training programs in low-income settings have shown limited, if any, impacts on firm revenues and profits, particularly for female entrepreneurs. This paper uses a randomized design to compare the impacts of two types of business training programs targeting women with established small businesses in urban Tanzania. The basic version of the training relied on in-class sessions to strengthen the managerial and technical skills of the participants. In the enhanced version, training was supplemented by individual visits from business coaches to the sites of participants’ activities, as well as other services tailored to their individual needs. The study finds no impact of the basic training on business practices and business outcomes. Participants in the enhanced training are more likely to adopt new practices, but show no effects for revenue or profits, on average. However, the average masks large heterogeneous effects: entrepreneurs with low levels of experience show reduced revenues; those with more experience benefit from the program. This finding suggests that business training programs may have greater impacts if they are more carefully targeted.